Dialektika Kecerdasan Buatan dan Akal Manusia: Tinjauan Kritis Epistemologi Pendidikan Ibnu Khaldun - Lhegina, Assyifa Qori; Maulaya, Rosendah Dwi (Universitas Pendidikan Indonesia, 2025)
AbstractThe massive integration of Generative Artificial Intelligence (AI) into the educational landscape has sparked an ontological crisis regarding the erosion of human cognitive autonomy. The instant convenience offered by algorithms threatens to distort the essence of learning from character formation into mere information transaction. This study aims to reconstruct Ibn Khaldun’s educational epistemology, specifically the concepts of Al-Fikr (thinking faculty) and Malakah (habit), as a critical framework to address the phenomenon of AI-induced cognitive offloading. Employing a qualitative approach with philosophical content analysis, this research juxtaposes the text of Al-Muqaddimah against contemporary literature on the psychological impacts of technology. The findings reveal a fundamental contradiction: while AI operates efficiently at the level of Al-‘Aql Al-Tamyizi (discriminative intellect), it lacks the capacity for Al-‘Aql Al-Tajribi (experimental intellect) and Al-‘Aql Al-Nazhari (speculative intellect), which require social embodiment and metaphysical reflection. The study concludes that the